Draft Genome Sequence of Williamsia sp. Strain D3, Isolated From the Darwin Mountains, Antarctica - Guerrero, Leandro Demián (2014)
Actinobacteria are the dominant taxa in Antarctic desert soils. Here, we describe the first draft genome of a member of the genus Williamsia (strain D3) isolated from Antarctic soil. The genome of this psychrotolerant bacterium may help to elucidate crucial survival mechanisms for organisms inhabiting cold desert soil systems.